(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2026)
The emission characteristics of epitaxial layers of GaAs and AlXGa1-XAs with the addition of the rare earth element Yb were determined using the photoluminescence method. In the exciton regions of AlXGa1-XAs epitaxial films, new photoluminescence maximum lines were determined for the doped ytterbium atoms. The influence of the ytterbium atom concentration on the change in the photoluminescence characteristics of GaAs and AlXGa1-XAs epitaxial films has been determined.